KOMUNIKASI SIMBOLIK DALAM UPACARA PERKAWINAN SUKU TOLAKI (STUDI DI DESA BENUA KECAMATAN AMONGGEDO KABUPATEN KONAWE) - Nur Mata Sari (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
ABSTRACT The problems that exist in this research is how the marriage symbolic communication Tolaki Tribe Village Sub Continent Amonggedo Konawe. As for the purpose of this study was to determine the symbolic communication Tolaki marriage Tribe Village Sub Continent Amonggedo Konawe. The informants are the traditional leaders, community leaders and religious leaders are often involved and know the ins and outs of marriage customs affairs Tolaki tribe. The number of informants in this study consisted of 3 traditional leaders, public figures 3 and 2 religious figures. Of this amount deemed to have represented proportionally based on the number of indigenous leaders, community leaders and religious leaders who know the procedures Tolaki tribe marriage customs. Continent village is a village located in the District of Amonggedo which have historically quite long and is one of the oldest villages in the district Amonggedo. In starting before the Dutch colonial period in the 1920s precisely roads and settlements have been arranged into 4 (four) the township is 4,490 m long Continent village, village Anahinunu 3450 Long, long Puasana 2,990 villages and hamlets Woerahi length of 3,690 m. In 1948 all four of the village on the move and are allocated on a rice field that is wide enough complex fed by Amonggedo times and in 1949 formed the village Amonggedo which includes four residential areas and villages.   Keywords : communication, simbolic, marriage, amonggedo